Ewolucja i aksjologiczne uzasadnienie dla wprowadzenia regulacji deweloperskich w polskim porządku prawnym - Pliszka, Natalia (PRAWO i WIĘŹ, 2025)
Contrary to common belief, the origins of development activity in Poland are not directly linked to the enactment of the first normative act regulating the relationship between the developer and the purchaser, namely the Developer Act of 2011. Nevertheless, it is indisputable that the emergence of professional entities currently referred to as developers dates back to the 1980s. Given the close interconnection between developer-specific regulations and other branches of law – particularly construction law, which to a significant extent delineates the direction of the sector’s development – this study undertakes an historical analysis of the evolution of legal norms impacting the real estate development sector. Taking into account that the Polish legal system is grounded in unilateral conventional acts established by duly authorized public authorities, it also proves essential to examine the process through which such entities came to recognize the necessity of adopting specific legal provisions governing the developer market. Accordingly, this article seeks to identify the axiological foundations underlying legislative changes and the implementation of new regulatory frameworks in the field of law pertaining to real estate development activity. The principal objective of this article is to demonstrate that the introduction of the first developer-specific regulations in Poland constituted a legislative response to practical issues arising in the performance of developer agreements (including the abuse of dominant positions by developers), rather than a catalyst for the sector’s growth.